Evernight - Gray, Claudia (New York : HarperTeen, 2008)
Sixteen-year-old Bianca, a new girl at the sinister Evernight boarding school, finds herself drawn to another outsider, Jared, but dark forces threaten to tear them apart and destroy Bianca's entire world.
Accelerated Reader AR